Phenotypic and Genotypic Study of Sodium Azide Effect on Proteus Mirabilis Swimming and Swarming Phenomenon - Luma Abd Alhadee (Journal of Global Pharma Technology, 2018)
The present study intended to detect the effect of sodium azide on P. mirabilis swimming and swarming phenomenon. Twenty one isolates of Proteus bacteria were collected from different clinical and animals samples for the period from October 2017 to November 2017. All isolates were identification depending on microscopic characterization , biochemical tests and Vitek 2E  compact system, it appears that eighteen  isolates were belong to P. mirabilis . All P. mirabilis isolates were able to swim and swarm over semi-solid media. The addition of sodium azide with (0.001, 0.01, 0.1) % concentrations was able to inhibit swimming and swarming phenomenon. Using PCR technique, WosA a gene responsible of swarming regulation was detected in all isolates and its expression was measured using RT-PCR in normal and sodium azide conditions. The result of molecular detection of WosA gene showed that all of the P. mirabilis isolates were possessed this gene and the levels of fold change of wosA gene were 0.19 and 0.12 for swimmer and swarmer cell respectively. The levels of fold change of wosA gene were 0.4 for the concentration (0.001%) of sodium azide when compared with control 1 fold change.Keywords: Proteus mirabilis, Swimming, Swarming, Sodium azide.